Reducing Writing Anxiety by Improving Self-Efficacy Beliefs (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Writing anxiety is an issue that affects students in all classes, but especially in writing-intensive courses like English language arts. Students with writing anxiety exhibit a range of behaviors, making it difficult for teachers to diagnose and prevent. Research has highlighted several possible solutions, but studies most consistently suggest improving students' writing self-efficacy beliefs as a means of reducing writing anxiety. Several research-based strategies, such as using peer reviews and the process writing approach, are useful in improving self-efficacy beliefs. Teachers should research the best strategies to reduce anxiety in their students, but should ultimately encourage students to believe that they can succeed.